Correlation between results obtained from four-point bending tests (4PBT) and double punch tests (DPT) in concrete reinforced with hooked-end steel fibers. (15th July 2021) - Carrillo, Julian; Torres, Diego; Guerrero, Hector
Highlights: Tensile performance of concrete reinforced with hooked-end steel fibers was assessed. Four-point bending tests (4PBT) and double Punch Tests (DPT) were carried out. DPT presents key advantages when compared to other indirect tests methodologies. Correlations between strength and toughness measured from 4PBT and DPT are proposed. Correlations allow describing the tensile performance of SFRC without resorting to 4PBT. Abstract: Most building codes prescribe the performance of steel fiber reinforced concrete (SFRC) from beam test results and, therefore, correlation models are required to estimate beam performance from more simplified tests such as double punch test (DPT). DPT provides advantages in terms of specimen size, equipment and simplified testing procedures. It also causes less variations in results, as compared to other methodologies of indirect tensile tests. The objective of this study is to propose correlations between SFRC's strength and toughness test results measured from 4PBT in beams and DPT in cylinders. The variables of the experimental program were the dosage and the number of hooks at the ends of the steel fibers. The proposed correlation models were developed from the results of the 80 samples tested in this study and the 34 additional tests reported in previous studies. Results from Analysis of Variance helped to identify that correlations between the strength from 4PBT and DPT can be used for SFRC with compressive strength varying between 21 and 45 MPa. Results from box-and-whisker analysis show that the mean value of the calculated to measured strength and toughness ratios, associated to the developed correlations, are lower than and close to unity, which indicates that the prediction provides conservative results and close to the measured values. The correlations were developed using a practical functional form that can be easily implemented in design codes.